2019
DOI: 10.3390/en12122233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Marine Synechococcus for an Algal Biorefinery in Arid Regions

Abstract: Implementing microalgae biorefinery in arid environments requires utilization of strains that can grow at high temperatures (above 28 °C) and salinity levels (above 30 ppt). In this study, we investigate the newly isolated seawater strain, Synechococcus, native to the United Arab Emirates, and evaluate its value as a perspective organism for cultivation (for fuel and bio-products) in regions with freshwater scarcity. The strain displayed tolerance to a wide range of temperature (22–37 °C) and salinity (20–41 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Algal culture technology is similar to terrestrial plants agriculture; however, algae possess higher productivity. Plants are in a different scale level with an evolved organisation of tissues, but micro and macroalgae have some advantages compared to them: they are not cultivated in agricultural soils, they can grow in non-potable water, in coastal, arid and marginal areas unsuitable for agricultural purposes (Cardon et al 2008;Gouveia and Oliveira 2009;Bochenski et al 2019). Moreover, considering the challenges and the agrozootechnical scenario of the coming years, the enlargement of feed resource base through identification of novel feeds or development of new additives that enhance resources use efficiency would play an important role in sustainable development of the animal productions.…”
Section: Introductionmentioning
confidence: 99%
“…Algal culture technology is similar to terrestrial plants agriculture; however, algae possess higher productivity. Plants are in a different scale level with an evolved organisation of tissues, but micro and macroalgae have some advantages compared to them: they are not cultivated in agricultural soils, they can grow in non-potable water, in coastal, arid and marginal areas unsuitable for agricultural purposes (Cardon et al 2008;Gouveia and Oliveira 2009;Bochenski et al 2019). Moreover, considering the challenges and the agrozootechnical scenario of the coming years, the enlargement of feed resource base through identification of novel feeds or development of new additives that enhance resources use efficiency would play an important role in sustainable development of the animal productions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bochenski et al 65 also stated that the marine isolate of Synechococcus sp. native to the United Arab Emirates demonstrated resistance to temperatures ranging from 22°C to 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bochenski et al 65 also stated that the marine isolate of Synechococcus sp. native to the United Arab Emirates demonstrated resistance to temperatures ranging from 22 C to 37 C. In line with previous research, 66 it was demonstrated that growing C. vulgaris cultures at 25 C may favor the carbohydrates production.…”
Section: Growth and Carbohydrate Accumulation Under Physical Conditionsmentioning
confidence: 99%